Upaya Peningkatan Penjualan dan Kemandirian Wirausahawan Golok Kecamatan Baros Kabupaten Serang - Ratu Erlina Gentari; Lina Marliana Dewi; Ade Nahdiatul Hasanah.,SE.,M.Akt; Suhartini (Universitas Serang Raya, 2021)
In Sukamenak village, the craftsmen manage their machetes and knives businesses independently, where they operate at home. The main problem to date has not been the formation of working groups or production houses that are professionally managed by certain institutions or offices to facilitate the efforts of these machete and knife craftsmen. In 1 day the craftsmen are able to make up to 15 machetes or ordinary knives, which will later be sold to the baros market and the attacking rau market, or sold to collectors with prices starting from Rp.30,000 depending on the size and shape of the machete. To increase the level of the community's economy by providing education and training. Entrepreneurship education activities carried out not only provide entrepreneurial skills, but also grow social capital to realize the formation of new entrepreneurs. Activities undertaken will be focused on forming one community group that will be empowered. The community will be given education and training through the management and marketing of machetes. The implementation method that will be carried out consists of five stages, namely: 1) counseling about the promotion and marketing of machetes as a business opportunity. 2) marketing training through digital marketing. 3) economic feasibility training through a good understanding of entrepreneurial management. 4) training marketing products online and offline markets. And 5) plans for the continuation of education and training activities.